INTEGRASI ILMU DAN AGAMA DALAM MENYONGSONG PERADABAN BANGSA - Aminah, Aminah (Universitas Islam Negeri Alauddin Makassar, 2017)
Abstract: The presence of a civilization is a necessity. In such efforts, the integration between science and religion is a basic framework that can facilitate such efforts. In this context, science is seen as something of a physical nature while religion is seen as something that is metaphysical. The synthesis between the two became a theo-anthropocentric assimilation that gave birth to the magnum opus of civilization.